Salidroside attenuates neuroinflammation and improves functional recovery after spinal cord injury through microglia polarization regulation - Wang, Chenggui; Wang, Qingqing; Lou, Yiting; Xu, Jianxiang; Feng, Zhenhua; Chen, Yu; Tang, Qian; Zheng, Gang; Zhang, Zengjie; Wu, Yaosen; Tian, Naifeng; Zhou, Yifei; et al. (Journal of cellular and molecular medicine, 2018)
Spinal cord injury (SCI) is a severe neurological disease; however, few drugs have been proved to treat SCI effectively. Neuroinflammation is the major pathogenesis of SCI secondary injury and considered to be the therapeutic target of SCI. Salidroside (Sal) has been reported to exert anti‐inflammatory effects in airway, adipose and myocardial tissue; however, the role of Sal in SCI therapeutics has not been clarified. In this study, we showed that Sal could improve the functional recovery of spinal cord in rats as revealed by increased BBB locomotor rating scale, angle of incline, and decreased cavity of spinal cord injury and apoptosis of neurons in vivo. Immunofluorescence double staining of microglia marker and M1/M2 marker demonstrated that Sal could suppress M1 microglia polarization and activate M2 microglia polarization in vivo. To verify how Sal exerts its effects on microglia polarization and neuron protection, we performed the mechanism study in vitro in microglia cell line BV‐2 and neuron cell line PC12. The results showed that Sal prevents apoptosis of PC12 cells in coculture with LPS‐induced M1 BV‐2 microglia, also the inflammatory secretion phenotype of M1 BV‐2 microglia was suppressed by Sal, and further studies demonstrated that autophagic flux regulation through AMPK/mTOR pathway was involved in Sal regulated microglia polarization after SCI. Overall, our study illustrated that Sal could promote spinal cord injury functional recovery in rats, and the mechanism may relate to its microglia polarization modulation through AMPK‐/mTOR‐mediated autophagic flux stimulation.